The use of municipal administrative sanctions by the municipalities of Brussels - Paul De Hert; Karen Meerschaut; Serge Gutwirth; Ann Vander Steene (Brussels Studies, 2008)
The laws of 1999 and 2004 concerning the implementation of municipal administrative sanctions (in short GAS legislation) gave local authorities new legal instruments to act more vigourously against phenomena of nuisance. Local authorities can now impose an administrative fine of up to 250 euros for behaviour which is contrary to public order (cleanliness, safety and quiet enjoyment) or which causes “public nuisance”. This publication purports to assess how the 19 municipalities of Brussels Capital Region formulate and apply this local “nuisance law”. Many differences emerge in terms of the content, the procedure and the modalities of municipal administrative sanctions (mediation, taking the minutes, amounts) and in terms of the choice between fines or police punishments. Even though some de facto harmonisation has taken place among Brussels police and security matters and the Region intervenes to make adjustments where necessary, the Brussels Region needs more institutionally-based guidance.